Oxidized phospholipids, linked to apolipoprotein B of oxidized LDL, are ligands for macrophage scavenger receptors - Kristin L. Gillotte; Sohvi Hörkkö; Joseph L. Witztum; Daniel Steinberg (Journal of Lipid Research, 2000)
Previous studies have shown that macrophage receptors for oxidized LDL (OxLDL) recognize both the lipid and protein moieties, and that a monoclonal antibody against OxLDL, EO6, also recognizes both species. The present studies show directly that during LDL oxidation phospholipids become covalently attached to apolipoprotein B (apoB). After exhaustive extraction of lipids, apoB of native LDL contained 4 ± 3 moles of phosphorus/mole protein. In contrast, apoB of OxLDL contained approximately 75 moles of phosphorus/mole protein. Saponification of this apoB released phosphorus, choline, and saturated fatty acids in a molar ratio of 1.0:0.98:0.84. When LDL was reductively methylated prior to oxidation, the amount of phospholipid covalently bound was reduced by about 80%, indicating that the phospholipids attach at lysine epsilon amino groups. Progressive decreases in the phospholipid associated with apoB of OxLDL decreased the ability of the protein to compete for binding to macrophage scavenger receptors and decreased its reactivity with antibody EO6. We postulate that some oxidized phospholipids containing fatty acid aldehydes at the sn-2 position bind to lysine residues of apoB while others remain unreacted within the lipid phase. This would account for the interchangeability of lipid and apolipoprotein of OxLDL with respect to receptor binding and antibody recognition.—Gillotte, K. L., S. Hörkkö, J. L. Witztum, and D. Steinberg. Oxidized phospholipids, linked to apolipoprotein B of oxidized LDL, are ligands for macrophage scavenger receptors. J. Lipid Res. 2000. 41: 824–833.